2016
DOI: 10.1051/matecconf/20164908001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between SARS CoV and MERS CoV Using Apriori Algorithm, Decision Tree, SVM

Abstract: Abstract. MERS (Middle EastRespiratory Syndrome) is a worldwide disease these days. The number of infected people is 1038(08/03/2015) in Saudi Arabia and 186(08/03/2015) in South Korea. MERS is all over the world including Europe and the fatality rate is 38.8%, East Asia and the Middle East. The MERS is also known as a cousin of SARS (Severe Acute Respiratory Syndrome) because both diseases show similar symptoms such as high fever and difficulty in breathing. This is why we compared MERS with SARS. We used dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…The results showed that elderly people are more likely to be infected than others. In [15], an SVM classifier based on sigmoid, normal and polynomial iterations was used to analyse the MERS and SARS proteins. The results showed their behaviour similarity and approximate dissimilarities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that elderly people are more likely to be infected than others. In [15], an SVM classifier based on sigmoid, normal and polynomial iterations was used to analyse the MERS and SARS proteins. The results showed their behaviour similarity and approximate dissimilarities.…”
Section: Discussionmentioning
confidence: 99%
“…In [13], the sample size is represented by articles collected from the Internet and reported by 153 news media outlets in Korea and the comments associated with these articles from day 1 (first confirmed case on May 20, 2015) to the day 70. In [15], the dataset contains 322 records, 92 infected cases and 230 uninfected cases. In [16], synthetic data are generated for 0.2 million users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study [48], to establish a disease prediction model, the Support Vector Machine (SVM), Decision Tree, and K-Nearest Neighbor (K-NN) classi cations were used on the MERS-CoV dataset, which included all reported cases in Saudi Arabia between 2013 and 2017. In a study [50], the researchers used three data mining algorithms of Apriori, Decision Tree, and SVM to compare and differentiate between two viruses with similar symptoms to SARS CoV and MERS CoV. They used the data of spike glycoprotein from NCBI.…”
Section: Data Miningmentioning
confidence: 99%
“…A study [16] applies three data mining algorithms to compare two viruses with similar symptoms: severe acute respiratory syndrome (SARS) and MERS coronaviruses. Apriori, Decision Tree, and SVM data mining algorithms are used on data of the spike in glycoprotein from the NCBI to distinguish between the two viruses.…”
Section: Literature Reviewmentioning
confidence: 99%